2016
DOI: 10.1093/mnras/stw121
|View full text |Cite
|
Sign up to set email alerts
|

Molecular gas kinematics within the central 250 pc of the Milky Way

Abstract: Using spectral-line observations of HNCO, N 2 H + , and HNC, we investigate the kinematics of dense gas in the central ∼ 250 pc of the Galaxy. We present scouse (Semi-automated multi-COmponent Universal Spectral-line fitting Engine), a line-fitting algorithm designed to analyse large volumes of spectral-line data efficiently and systematically. Unlike techniques which do not account for complex line profiles, scouse accurately describes the {l, b, v LSR } distribution of Central Molecular Zone (CMZ) gas, which… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
270
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(291 citation statements)
references
References 100 publications
(281 reference statements)
19
270
1
Order By: Relevance
“…Thus, the turbulent velocity dispersion is significantly smaller than the total velocity dispersion. Henshaw et al (2016) recently measured a 1D velocity dispersion of -11 km s 1 for G0.253+0.016, 25% higher than our estimate that includes the contribution of the large-scale gradient. This difference arises because Henshaw et al (2016) measured the LOS velocity dispersion, while we measure the dispersion in the plane of the sky.…”
Section: Velocity Pdfcontrasting
confidence: 78%
See 1 more Smart Citation
“…Thus, the turbulent velocity dispersion is significantly smaller than the total velocity dispersion. Henshaw et al (2016) recently measured a 1D velocity dispersion of -11 km s 1 for G0.253+0.016, 25% higher than our estimate that includes the contribution of the large-scale gradient. This difference arises because Henshaw et al (2016) measured the LOS velocity dispersion, while we measure the dispersion in the plane of the sky.…”
Section: Velocity Pdfcontrasting
confidence: 78%
“…We further correct for the large-scale gradient. However, the LOS velocity dispersion includes the contributions from the large-scale gradient and thus the dispersions and Mach numbers determined in Henshaw et al (2016) are not the purely turbulent dispersions and Mach numbers.…”
Section: Velocity Pdfmentioning
confidence: 99%
“…Walsh et al 2011, Purcell et al 2012. They have a spatial resolution of ∼ 60 arcsec and a spectral resolution of 2 km s −1 , and have been fit using the Semi-automated multi-COmponent Universal Spectralline fitting Engine (SCOUSE, Henshaw et al 2016, https://github.com/ jdhenshaw/SCOUSE).…”
Section: Numerical Schemementioning
confidence: 99%
“…High resolution molecular line studies of the CMZ have revealed coherent features spanning the width of the (l, b, v) data cubes in several different species, including CO, CS, NH 3 and HNCO (Nagayama et al 2007;Oka et al 2007;Henshaw et al 2016b). The origin of these features has been of interest for several decades, and proposed explanations include two spiral arms (Sofue 1995;Sawada et al 2004), a twisted elliptical orbit (Molinari et al 2011), or an open stream (Kruijssen et al 2015).…”
Section: Introductionmentioning
confidence: 99%